(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article argues that in any multiethnic state, one of the main indicators of a democratic society, the state of interethnic relations, internal security and political stability of the country is religious tolerance and interfaith harmony. We are talking about the existence in society of religious tolerance, interethnic harmony, mutual understanding of people of different religions, language, culture, customs, traditions and values of other religions and nationalities, as well as the legal mechanisms that regulate them